2003
DOI: 10.1289/ehp.5519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of submicrometer particle compositions on cytokine production and lipid peroxidation of human bronchial epithelial cells.

Abstract: To identify the size and components related to toxicity of ambient particles, we used a trichotomous impactor to collect 17 sets of particles in three size ranges--submicrometer (diameters < 1 microm; PM1.0, fine (diameters between 1 and 2.5 microm; PM1.0-2.5, and coarse (diameters between 2.5 and 10 microm; PM2.5-10--at stations monitoring background, urban, traffic, and industrial air in Taiwan. Elemental contents, carbon contents, soluble ions, and endotoxin content of particles were determined by X-ray flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 21 publications
3
54
0
Order By: Relevance
“…A consistent association between levels of particulate matter in the ambient air and increases in mortality due to respiratory and cardiovascular complications has been reported (Salvi et al, 1999;Kleinman et al, 2000;Huang, Hsu, and Chan, 2003;Pozzi et al, 2003). Therefore, the effects of acid-washed PM 1648, PM 1648, PM 2.5 , and saline on mortality in NZM mice were examined.…”
Section: Effects Of Particulate Matter On Mortality Proteinuria and mentioning
confidence: 62%
See 4 more Smart Citations
“…A consistent association between levels of particulate matter in the ambient air and increases in mortality due to respiratory and cardiovascular complications has been reported (Salvi et al, 1999;Kleinman et al, 2000;Huang, Hsu, and Chan, 2003;Pozzi et al, 2003). Therefore, the effects of acid-washed PM 1648, PM 1648, PM 2.5 , and saline on mortality in NZM mice were examined.…”
Section: Effects Of Particulate Matter On Mortality Proteinuria and mentioning
confidence: 62%
“…However, pulmonary toxicity and fibrosis have been reported with urban particles with the greatest toxicity seen with PM 2.5 (Churg and Brauer, 2000;Schwartz and Neas, 2000;van Zijverden et al, 2001;Buerke et al, 2002). Also, there has been a consistent link between increased incidence of mortality and morbidity due to cardiopulmonary complications and elevated levels of particulate matter in the air (Salvi et al, 1999;Kleinman et al, 2000;Huang, Hsu, and Chan, 2003;Pozzi et al, 2003). We also demonstrated that PM 1648 and PM 2.5 exposed NZM mice showed increases in fibrosis, collagen deposition, and immune cell infiltration in the lungs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations